(untitled) (International Journal of Environmental Sciences, 2025)
The human gut microbiome is a complicated ecosystem that is very important for the health of the host because it affects metabolism, immunity, and disease prevention. Prebiotics are substances that some bacteria in the host use preferentially to improve health. They are very important for changing this microbial ecology. This review looks at the growing potential of mucilages and extracts from plants as new sources of prebiotics. It goes into detail about their different chemical makeups, how they work (through selective fermentation, short-chain fatty acid production, and targeted microbial modulation), and the many health benefits they have, such as better immune function, better gastrointestinal health, better metabolic health, and better neurological health. The paper uses evidence from research on cells, animals, and people to show how different plant sources, like chia, flaxseed, okra mucilage, and polyphenol-rich extracts from chicory, garlic, and grape seed, are different from each other. The current problems, such as the necessity for standardization and strong human clinical studies, are talked about. Advanced extraction methods, tailored nutrition, and synergistic synbiotic formulations are all important areas for future research. These natural substances have the potential to change the way we think about gut health and general health.